Students' Islamic approach on ibadah: a structural modelling approach. - Ismail, Nik Ahmad Hisham; Tekke, Mustafa; othman, Nooraini; Abd Razak Al-Hafiz, Afareez (Elsiver Ltd, 2016)
The aim is to investigate the structure of Ummatic Personality Inventory. The sample selected was n=287 students in government secondary schools. The findings show that Fardhu Ain correlated with Fardhu Kifayah.. More efforts should be initiated at school level for educating students to be close to God and follow the teaching of the Prophet s.a.w.